2009
DOI: 10.2471/blt.07.049841
|View full text |Cite
|
Sign up to set email alerts
|

Do lifestyle interventions work in developing countries? Findings from the Isfahan Healthy Heart Program in the Islamic Republic of Iran

Abstract: Objective To assess the effects of a comprehensive, integrated community-based lifestyle intervention on diet, physical activity and smoking in two Iranian communities. Methods Within the framework of the Isfahan Healthy Heart Program, a community trial was conducted in two intervention counties (Isfahan and Najaf-Abad) and a control area (Arak). Lifestyle interventions targeted the urban and rural populations in the intervention counties but were not implemented in Arak. In each community, a random sample of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(101 citation statements)
references
References 40 publications
4
95
0
2
Order By: Relevance
“…The study showed that GPs who received the education-based intervention attained improved clinical competence compared with the control group and achieved significantly better BP control and preservation of kidney function in their patients. Similar levels of benefit have been reported in studies that have assessed education-based hypertension management strategies in broader patient groups in developing countries (22,23), many of whom are at high risk of developing CKD. For example, in the COBRA Trial (19), the study from which the study by Jafar et al (16) derives its cohort, a reduction in BP of almost 11 mmHg at the end of the trial in the group that received the HHE and GP training intervention was reported.…”
supporting
confidence: 71%
“…The study showed that GPs who received the education-based intervention attained improved clinical competence compared with the control group and achieved significantly better BP control and preservation of kidney function in their patients. Similar levels of benefit have been reported in studies that have assessed education-based hypertension management strategies in broader patient groups in developing countries (22,23), many of whom are at high risk of developing CKD. For example, in the COBRA Trial (19), the study from which the study by Jafar et al (16) derives its cohort, a reduction in BP of almost 11 mmHg at the end of the trial in the group that received the HHE and GP training intervention was reported.…”
supporting
confidence: 71%
“…The programme comprised 10 distinct projects, each targeted to different fields and groups, one of which was HFHC (7,8). In terms of healthier nutrition, main emphasis was put on activities toward changing the dietary environment of the population.…”
Section: Methodsmentioning
confidence: 99%
“…The IHHP objectives were described in details elsewhere. Healthy Food for Healthy Communities (HFHC) was a component of IHHP project, consisting of a wide variety of strategies, including initiatives regarding oil consumption and labelling as well as intake of healthy bread (7,8,9,10).…”
Section: Introductionmentioning
confidence: 99%
“…In the second stage, based on the results of surveys conducted in the first phase, the interventions including 10 projects (women, children, youth, individuals in worksite, health workers, non-governmental organizations and volunteers, high risk individuals, cardiovascular patients and nutrition and exercise project)was begun in1380 in the total population. These intervention projects are described in table1 [15]. Interventions were performed in three groups including health workers, the general public (children and adults) and high risk individuals.…”
Section: Healthy Lifestyle For Cardiovascular Patients Projectmentioning
confidence: 99%